Insurgent quavers: Uses and functions of FARC-EP music during the armed conflict in Colombia (2020)
This article analyzes the uses and functions that the music produced by the FARC-EP had for the organization and its political-military work during the armed conflict in Colombia. Based on the review of primary and secondary sources, participant observation in 6 'fariano concerts' and 14 interviews, it is affirmed that Fariano music -as sound and practice- fulfilled fundamental role to strengthen the social and ideological cohesion of the FARC-EP, to motivate and inspire its members and to sustain a collective identity both in the countryside and in the cities. Regarding the political work of the insurgency with civil society, music was used to entertain, generate sympathy and add solidarity. © 2020 Ariadna Ediciones. All rights reserved.